2002
DOI: 10.1128/jvi.76.19.9716-9723.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Adenovirus E3 RID Complex Protects Some Cultured Human T and B Lymphocytes from Fas-Induced Apoptosis

Abstract: Human group C adenoviruses cause an acute infection in respiratory epithelia and establish a long-term or persistent infection, possibly in lymphocytes. The mechanism by which this persistence is maintained is unknown; however, it would require that persistently infected lymphocytes not be deleted. The adenovirus genome encodes proteins that prevent the immune system from eliminating the virus-infected cell, including the E3 receptor internalization and degradation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Ads establish longterm, latent infections of mucosal lymphocytes associated with intermittent virus shedding in stool (89). It has been suggested that E3 proteins, including RID␣, prevent the elimination of persistently infected lymphocytes by downregulating expression of receptors involved in innate immune responses (90). Our results suggest that RID␣ may also induce limited changes in gene expression that mimic a developmental program regulating B cell differentiation, by upregulating constitutive NF-B activity in persistently infected lymphocytes.…”
Section: Discussionmentioning
confidence: 58%
“…Ads establish longterm, latent infections of mucosal lymphocytes associated with intermittent virus shedding in stool (89). It has been suggested that E3 proteins, including RID␣, prevent the elimination of persistently infected lymphocytes by downregulating expression of receptors involved in innate immune responses (90). Our results suggest that RID␣ may also induce limited changes in gene expression that mimic a developmental program regulating B cell differentiation, by upregulating constitutive NF-B activity in persistently infected lymphocytes.…”
Section: Discussionmentioning
confidence: 58%
“…Retroviruses were produced as described previously (41). Briefly, the vector control LXSN or the LXSN-CAR plasmids were transfected into BOSC23 cells using FuGene6 transfection reagent (Roche) following the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The HAdV-C E3 14.7K protein inhibits cell lysis by tumor necrosis factor alpha (TNF-␣) and lymphotoxin (54)(55)(56). CR1␣, RID␣, and RID␤ cooperate to evade TNF-␣-related apoptosis through TRAIL (57)(58)(59)(60), and the RID complex independently mediates loss of cell surface Fas (58,61), blocks TNF-␣-induced NF-B activation (62)(63)(64), and downregulates the epidermal growth factor receptor (40,65). HAdV-C CR1␤ (66), also called the adenovirus death protein, is expressed at greatest abundance late in infection (67) and is required for efficient cell lysis (68) and viral spread (69) in the final phase of viral infection.…”
mentioning
confidence: 99%